Effect of hypopressive and conventional abdominal exercises on postpartum diastasis recti: A randomized controlled trial. - Mercedes Soto-González; Iria Da Cuña-Carrera; Eva María Lantarón-Caeiro; Augusto Gil Pascoal (PLoS ONE)
Background Diastasis recti abdominis (DRA) is the separation of the rectus abdominis muscles along the linea alba, often occurring during pregnancy due to hormonal and mechanical changes. While DRA usually resolves post-childbirth, some women experience persistent issues. Exercise may help reduce the inter-rectus distance, though more research is needed. Objectives Analyze the immediate and long-term effects of hypopressive and conventional abdominal exercises on inter-rectus distance (IRD) in postpartum women, focusing on parity differences. Methods Twenty-eight women who met specific inclusion criteria were randomly assigned to either the hypopressive group (n = 14) or the conventional group (n = 14). The exercise programs for both groups lasted 6 weeks. Ultrasound measurements were taken of the IRD at two locations above the umbilicus, 2 cm (AB2) and 5 cm (AB5), before and after exercise programs. Results The IRD decreased after both exercise programs compared to baseline measurements in AB2 (mean difference: 3.06 mm, 95% CI: 1.06 to 5.05) and in AB5 (mean difference: 2.88 mm, 95% CI: 1.59 to 4.17), confirming the long-term effect of exercise. No differences were found between the application of the conventional exercise program or the hypopressive exercises, indicating that both had a similar positive effect. Regarding the immediate effect, after the performance of both programs, the IRD was greater during rest compared to abdominal contraction. This effect was more pronounced at AB5 location (mean difference: 1.00mm, 95% CI: 0.97 to 1.89). Conventional exercises result in a reduction during resting condition (mean difference: 4.52mm, 95% CI: 2.62 to 6.79), whereas with hypopressive exercises, the reduction occurs during muscle contraction (mean difference: 3.43mm, 95% CI: 1.21 to 5.65). With regard to parity, multiparous women benefit most from the application of exercise programs. Conclusion A reduction in IRD has been achieved with the implementation of both exercise programs in postpartum women, with multiparous women benefiting the most. Specifically, at 5 cm above umbilicus, conventional exercises result in a reduction during the rest condition, whereas with hypopressive exercises, the reduction occurs during muscle contraction. Trial registration Clinical trial registration: NCT05439668.